Respuestas

2014-01-15T22:18:45+01:00
a)  (-3)2.2-(2-3)3+5:(-5)-32-3.(-1) =
b) (-2)3:(-2)2+(42-3.5)2-8:(-4)-2.(-5) =
c) (3-2.4)0-5.(-2)2.(-3)+(5-7).(22+3.2)+3.(-1) =
d) (6.5-33).2-[(3-3.2)2+(5.2-12)3]+(-6)2 =e) [5+2.(-4)]2: (-3)-[5.(-4)+(-6)]-(-1)=f) {2.(-5):(-1)+8.(-4)-20+[(-1)3]4}2-10.(-1)+7.(-8) =
g) [(17 − 15)3 + (7 − 12)2] : [(6 − 7) · (12 − 23)] =
h) (5 + 3 · 2 : 6 − 4 ) · (4 : 2 − 3 + 6) : (7 − 8 : 2 − 2)2 =
  • Usuario de Brainly
2014-01-15T22:22:42+01:00
Resuelve:
5 + [-2 + (-4)*(-3)³] : (-2) - (-5)² - (+4)* [(-6) - (-3)*3] = 

[(+5)*(-2)² + (-3)*(-2)] - [3³ + (-5)*(-8)] = 

[(-2)*(+3) - (-4)] + [3² + (-5)] =